Geopolitical Perspective, in The Relations of the U.S. And Iraqi Kurdistan Region Since 2003 - Arez Abdulqader Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This article focuses on the geopolitical perspective, in the relations between America and Iraqi Kurdistan Region since 2003. Since then, the Iraqi Kurdistan Region has become a good ally of the U.S. because the region geopolitically is significant for the United State foreign policy. The Iraqi Kurdistan Region has been using its strategic location in order to enhance its relations with the U.S. The purpose of the study is to explore the significance of geopolitical perspective in the U.S. and KRI relations since 2003. This paper examines that by focusing on two main factors. Firstly, the military relations between the U.S. and the IKR, which are the Iraq war in 2003 and the Islamic State war since 2014. Secondly, security and stability of the Iraqi Kurdistan Region. This research aims to answer the main question: dose geopolitical perspective influence on relations between the U.S. and the Iraqi Kurdistan Region? This research concludes that for the US the geopolitical of KRI is significant. Ultimately, it appears that there is a good relationship between the U.S. and the Iraqi Kurdistan Region.